Integrating genetic subtypes with PET scan monitoring to predict outcome in diffuse large B-cell lymphoma - Matías S. Mendeville; Jurriaan Janssen; G. Tjitske Los-de Vries; Erik van Dijk; Julia Richter; Marcel Nijland; Margaretha G. M. Roemer; Phylicia Stathi; Nathalie J. Hijmering; Reno Bladergroen; Diego A. Pelaz; Arjan Diepstra; et al. (Nature Communications)
Abstract Next Generation Sequencing-based subtyping and interim- and end of treatment positron emission tomography (i/eot-PET) monitoring have high potential for upfront and on-treatment risk assessment of diffuse large B-cell lymphoma patients. We performed Dana Farber Cancer Institute (DFCI) and LymphGen genetic subtyping for the HOVON84 (n = 208, EudraCT-2006-005174-42) and PETAL (n = 204, EudraCT-2006-001641-33) trials retrospectively combined with DFCI genetic data (n = 304). For all R-CHOP treated patients (n = 592), C5/MCD- and C2/A53-subtypes show significantly worse outcome independent of the international prognostic index. For all subtypes, adverse prognostic value of i/eot-PET-positive status is confirmed. Consistent with frequent primary refractory disease, only 67% C2 patients become eot-PET-negative versus 81-88% for other subtypes. Indicative of high relapse rates, outcome of C5 i/eot-PET-negative patients remains significantly worse in HOVON-84, which trend validates in the PETAL and SAKK38-07 trials (NCT00544219). These results show the added value of integrated genetic subtyping and PET monitoring for prognostic stratification and subtype-specific trial design.